2017
DOI: 10.14260/jemds/2017/1246
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Portal Vein Diameter and Splenic Size With Oesophageal Varices in Cirrhosis of Liver

Abstract: BACKGROUND Portal hypertension is one of the serious complications of cirrhosis of liver leading to unwanted life-threatening variceal bleeding. Loss of liver architecture and fibrosis lead to increased resistance to blood flow through portal vein causing portal hypertension and ultimately leading to ascites, oesophageal varices and splenomegaly. The aim of the study is to find out correlation of portal vein diameter and splenic size with oesophageal varices in cirrhosis of liver. MATERIALS AND METHODS A descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
1
8
1
Order By: Relevance
“…In contrast to Mohanty et al [16] who found a definite correlation between the increase in splenic size and portal vein diameter with the severity of EVs, our results showed no significant differences between patients with mild or moderate EVs and those with severe EVs regarding spleen diameter as well as portal vein diameter.…”
Section: Figurescontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to Mohanty et al [16] who found a definite correlation between the increase in splenic size and portal vein diameter with the severity of EVs, our results showed no significant differences between patients with mild or moderate EVs and those with severe EVs regarding spleen diameter as well as portal vein diameter.…”
Section: Figurescontrasting
confidence: 99%
“…In our study, there were significant differences between patients who had EVs and those hadn't, regarding spleen diameter as well as portal vein diameter, this constant with Mohanty et al [16] who found that portal vein diameter and splenic size were increased in patients with EVs than patients without EVs.…”
Section: Figuressupporting
confidence: 83%
“…The portal vein diameter in this study was larger in patients with CLD than their age-matched controls. Previous studies conducted [19][20][21][22][23][24] also reported an increase in the diameter of the portal vein in patients with CLD. Another study 25 opined that patients with a portal vein diameter greater than 12 mm were more predisposed to having portosystemic collaterals.…”
Section: Discussionmentioning
confidence: 78%
“…Figure 3 depicts the comparison between PVD and PC/SD ratio regarding their sensitivity, specificity and accuracy in predicting OV. [11][12][13][14] This high prevalence of OV on endoscopy may be due to the delay in seeking treatment after signs and symptoms of portal hypertension have developed.…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with our study, Mohanty et al also reported a mean PVD of 13.46±0.98 mm in the group with OV, which was significantly higher in comparison to the group without OV with 10.91±0.65 mm. 12 In a study by Bhattarai et al and Sreenath et al significant association was seen between OV and PVD. 15,16 Makarem et al also reported that PVD was higher in cirrhotic patients with OVs, but this correlation failed to reach statistical significance.…”
Section: Portal Vein Diametermentioning
confidence: 91%